Recognizing the Complexity and Richness of African American English (AAE) as Literate Language - Horton, RaMonda; Clark, Kimberline G. (Seminars in Speech and Language, 2025)
The purpose of this article is to provide the readers of the forum with an overview of research on African American children's language and connection to literacy, review how literate language has been traditionally defined and conceptualized, describe areas of concern when using traditional perspectives on literate language to evaluate the language of African American English (AAE) speakers, and recommend assessment approaches and strategies that allow for a comprehensive assessment that is informed by sociocultural orientations to literacy.
Keywords: AAE; literate language; assessment